Outcomes of anti-Müllerian hormone-tailored ovarian stimulation protocols in in vitro fertilization/intracytoplasmic sperm injection cycles in women of advanced age - Chi-Chun Liao; Robert Kuo-Kuang Lee; Shyr-Yeu Lin; Ming-Huei Lin; Yuh-Ming Hwu (Elsevier, 2016)
Objective: We aimed to compare the outcomes of in vitro fertilization/intracytoplasmic sperm injection (IVF/ICSI) treatments in women of advanced age (>40 years) using anti-Müllerian hormone (AMH)-tailored ovarian stimulation protocols versus conventional protocols based on antral follicle count (AFC). Materials and Methods: We retrospectively reviewed 210 women who underwent IVF/ICSI cycles: 116 women underwent stimulation protocols that were tailored to their AMH levels, whereas 94 women received treatment using conventional stimulation protocols based on AFC as the ovarian reserve marker. Results: The following parameters were significantly higher in the AMH-tailored group than in the conventional group: initial and total doses (IU) of recombinant follicle-stimulating hormone (rFSH) used for stimulation (514.2 ± 137.9 vs. 452.3 ± 135.3, p = 0.001; 4713.8 ± 1618.8 vs. 4047.2 ± 1366.0, p = 0.007, respectively), ovum pick-up rate (OPU; 88.8% vs. 75.5%, p = 0.016), serum estradiol (E2) level on the day of human chorionic gonadotropin (hCG) administration (1818.5 ± 1422.4 vs. 1394.0 ± 929.0 pg/mL, p = 0.028), number of oocytes retrieved (7.4 ± 5.1 vs. 5.5 ± 3.4, p = 0.007), number of embryos per case (4.2 ± 3.2 vs. 3.3 ± 2.5, p = 0.048), clinical pregnancy rates (22.4% vs. 8.5%, p = 0.008), implantation rates (13.1% vs. 3.9%, p = 0.001), and live birth rates per cycle (15.5% vs. 6.4%, p = 0.049). Conclusion: Individualized controlled ovarian stimulation (COS) protocols tailored to patients' AMH levels may improve the pregnancy rate, implantation rate, and live birth rate in women of advanced age undergoing IVF/ICSI compared with those receiving conventional stimulation protocols.